Absorption of Fluorinated Greenhouse Gases in Deep Eutectic Solvents - Castro, Paulo J. (2020)
The environmental impact resulting from the release of fluorinated gases (F-gases), commonly used in refrigeration, is prompting the development of technologies to recover and recycle them. Fluorinated ionic liquids (FILs) have been investigated as promising candidates for the absorption and selective separation of F-gases. In this work, we prepared deep eutectic solvents (DESs) composed of FILs and perfluorinated acids to explore the excellent gas solubilization properties of FILs with high melting points in a wider liquid range. A screening of DESs prepared from five different FILs was performed for the solubilization of 1,1,1,2-tetrafluoroethane (R-134a) at 303.15 K, using a stainless steel volumetric system. [N4444][C4F9SO3]/C4F9CO2H and [C2C1Im][C8F17SO3]/C4F9CO2H were selected as the systems with the best absorption capacities and were studied in three different molar ratios of FIL/perfluorinated acid. Then, the absorption of difluoromethane (R-32), pentafluoroethane (R-125), and R-134a were determined at 303.15, 313.15, and 323.15 K. All studied DESs have high selectivity for the separation of R-134a from their mixtures with the other two F-gases. The results presented here provide knowledge of the behavior of these new alternative solvents for the separation of F-gases from commercial refrigerants, at three different temperatures, and in a wide range of operating pressures.